New mechanism for the cosmological red-shift explaining: non-observation of dark energy, large-number- coincidence and the cosmic coincidence - Tank, Hasmukh K. (International Journal of Advanced Astronomy, 2015)
Accepting Einsteinâ€™s General Relativity Theory, that the changes in the gravitational field can propagate at the speed of light, it is proposed here that: before an electron in an atom emits a photon, the energy (h f0) of the photon was a part of total energy of the atom; contributing to establish the gravitational-field around the atom. As soon as an electron in that atom emits a photon of energy h f0, and the photon starts moving away from the atom, the gravitational-field around the atom partly reduces, proportional to the photonâ€™s energy h f0, and this wave of â€˜reduced gravitational fieldâ€™ propagates radially-outwards at the speed of light. And a part of energy of the photon gets spent in â€œfillingâ€ the â€˜gravitational potential-wellâ€™ produced by its energy, when it was a part of energy of the atom. From the derivation presented here we find that the energy spent by the photon to â€œfillâ€ the â€˜gravitational potential-wellâ€™, during its inter-galactic journey manifests as the â€˜cosmological red-shiftâ€™. And the so called â€˜total-mass-of-the-universe'â€™ and â€˜radius-of-the-universe'â€™ are just mathematically-equivalent mass and distance arising while converting electrostatic potential-energy into gravitational potential-energy. This is the reason why we find the large-number-coincidence (LNC). And since there is no expansion of the universe, there is no â€˜cosmic coincidenceâ€™, that why only in this epoch we find the â€˜large-number-coincidenceâ€™!